Image of Lithuania in Jean Mauclèreʾs Travel Books - Dručkutė, Genovaitė (Literatūra, 2016)
The French writer and jornalist Jean Mauclère (1887–1951), who developed an interest in Lithuania in his youth, visited Lirhuania twice, and devoted much of his writing to it. His interest in Lithuania bloomed into books on history and literature, transcripts of folktales, travel books, a number of articles in French media. They received positive critical reception in France at time. The article discusses the image of Lithuania in Jean Mauclèreʾs travel books Sous le ciel pâle de Lithuanie (Paris, Plon-Nourrit, 1926) and Gens et routes de Lithuanie (Paris, A. Redier, Librairie de la Revue française, 1931). As the narrator travels through Lithuania, he meets politicians, public figures, writers, artists and so-called common people. He discusses the economic (industry, agriculture) and cultural (education, literature, art) developments in Lithuania, reflects on Lithuaniaʾs landscape, the physical type of its resident, and the features of the Lithuanian language. The narrator notes the regional differences; he not only focuses on the nation at large, but also considers national minorities. The narrative on Lithuania, wchich at the time was undergoing the process of modernization, captures the images of the past, legends, the continuous relationship between past and present. The narrator offers an absorbing parallel between the two most important Lithuanian cities of Kaunas and Vilnius. The narrator of travel books, an educated writer and journalist, representative of Western Europe, reflects on Lithuania in a favourable and optimistic manner. He emphasizes the European character of Lithuania, its modernity, dwells on its exotic nature. The narrator suggests that the latter feature defines Lithuania’s authenticity among other Wester European states. The analysis of the image of Lithuania in Mauclère’s travel books draws on the premises of comparativist imagology (Yves Clavaron, Jean-Marc Moura, Daniel Henry Pageux, Pierre Rajotte etc.).